Flame of love : a theology of the Holy Spirit - Pinnock, Clark H., 1937- (Downers Grove, Ill. : InterVarsity Press, 1996)
In what may be regarded as his magnum opus, Clark Pinnock turns attention to the vital Christian doctrine of the Holy Spirit. Writing out of both wide learning and deep personal passion, he shows the way to restore the oft neglected Spirit to centrality in the life and witness of the church. Pinnock explores the doctrine of the Spirit in relation to other key doctrines such as the Trinity, creation, Christology and the church. Never one to duck the difficult or sensitive.
questions, he also explores issues of the Spirit's universality, gender language for the Spirit and charismatic gifts. Pinnock intends his book to be catholic (in the sense of respecting the beliefs and worship of the historic church) and evangelical (drawing particularly on the heritage of the Reformation). Always in sight is the mission of the church, for "people want to meet the real and living God and will not be satisfied with a religion that only preaches and.
moralizes. Even the unchurched sense that knowing about God is not the same as knowing God....Only by attending to the Spirit can we move beyond sterile rationalist religion in the direction of recovering the sense of intimacy and immediacy for which our generation - and every generation - longs."
Spirit & Trinity -- Spirit in creation -- Spirit & Christology -- Spirit & church -- Spirit & union -- Spirit & universality -- Spirit & truth.
Includes bibliographical references (p. [249]-280).
Keywords: Holy Spirit